A novel strategy for low level laser-induced plasmonic photothermal therapy: the efficient bactericidal effect of biocompatible AuNPs@(PNIPAAM-co-PDMAEMA, PLGA and chitosan) - Gharatape, Alireza; Milani, Morteza; Rasta, Seyed Hossein; Pourhassan-Moghaddam, Mohammad; Ahmadi-Kandjani, Sohrab; Davaran, Soodabeh; Salehi, Roya (RSC advances, 2016)
Nowadays the control of multidrug resistant (MDR) and pandrug resistant (PDR) bacteria has been the subject of extensive research. In this study an effective strategy was developed to destroy bacteria using low-level laser photothermal therapy combined with biocompatible surface-modified AuNPs. First, chitosan, poly( N -isopropylacrylamide)- co -(2-dimethylamino ethyl methacrylate) P(NIPAAM- co -DMAEMA) and poly(lactic- co -glycolic acid) (PLGA) modified AuNPs were synthesized and fully characterized. Afterwards, P. aeruginosa and A. baumannii (Two Gram-negative strains of bacteria) were exposed to different doses of low level NIR laser (810 nm) radiation in the presence or absence of the as-prepared surface-modified AuNPs (in a 1 : 1 ratio) and the killing efficiency of the radiated laser doses was calculated based on pour-plate colony count for each condition. Chitosan, P(NIPAAM- co -DMAEMA) and PLGA modified AuNPs were synthesized with a core/shell size of 108, 10 and 120 nm, respectively which was confirmed with DLS and TEM studies. Successful polymerization and surface coating of AuNPs was confirmed by FT-IR and 1 H NMR. A decreasing trend in the viability of both bacteria was observed along with an increase of the laser dose for all three types of polymer-coated AuNPs. PLGA@AuNPs exhibited the most effective NIR-induced photothermal killing on both bacteria. In other words, 10 J cm −2 and 30 J cm −2 doses were enough to destroy almost all P. aeruginosa , and A. baumannii , respectively. Our study suggests the usefulness of low-level laser in plasmonic photothermal treatment. The suggested strategy, as a new method of anti-bacterial intervention, can be used for the eradication of infections such as wound infections in order to accelerate the healing process. In addition, the offered strategy can be suggested in the treatment of other bio-threats such as cancerous diseases in vivo .